2018
DOI: 10.1029/2018jc014037
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Kinetic Energy in the Arctic Ocean's Beaufort Gyre

Abstract: Kinetic energy (KE) in the Arctic Ocean's Beaufort Gyre is dominated by the mesoscale eddy field that plays a central role in the transport of freshwater, heat, and biogeochemical tracers. Understanding Beaufort Gyre KE variability sheds light on how this freshwater reservoir responds to wind forcing and sea ice and ocean changes. The evolution and fate of mesoscale eddies relate to energy pathways in the ocean (e.g., the exchange of energy between barotropic and baroclinic modes). Mooring measurements of hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…A general anticyclonic PWW circulation during 2003–2016 is shown in Figure . The depth‐averaged velocity in 100–200 m shows similar circulation pattern (Zhao et al, ). Mooring B is dominated by a northeastward current, mooring C southeastward current, and mooring D southwestward current, while mooring A does not show a clear preference of current direction likely because it is close to the center of BG (which is revealed in the following discussion of freshwater content distribution).…”
Section: Resultsmentioning
confidence: 53%
“…A general anticyclonic PWW circulation during 2003–2016 is shown in Figure . The depth‐averaged velocity in 100–200 m shows similar circulation pattern (Zhao et al, ). Mooring B is dominated by a northeastward current, mooring C southeastward current, and mooring D southwestward current, while mooring A does not show a clear preference of current direction likely because it is close to the center of BG (which is revealed in the following discussion of freshwater content distribution).…”
Section: Resultsmentioning
confidence: 53%
“…Overall, the regional freshwater content increased by ~40% (i.e., 6,400 km 3 ) from 2003 to 2018, at a rate of approximately 4,420 ±1,300 km 3 per decade. These overall, seasonal, interannual, and longer term fluctuations depend on the complicated interplay of wind, ice, and ocean dynamics and thermodynamics regulating Beaufort Gyre spin‐up, dissipation, and stabilization (see for details Kelly, Proshutinsky, Popova et al, ; Liang & Losch, ; Manucharyan & Isachsen, ; Mensa et al, ; Regan et al, ; and Zhao et al, , etc., in this special collection).…”
Section: Interannual Changes Of Freshwater Contentmentioning
confidence: 99%
“…It is concluded that without sea ice the major features of these dynamics resemble characteristics in the midlatitudes. The subsurface mesoscale eddy field is studied by Zhao et al () using horizontal water velocities measured by BGOS moorings. Partitioning of kinetic energy into barotropic and baroclinic modes suggests that the halocline structure plays a specific role in limiting the capacity for frictional dissipation at the sea floor.…”
Section: Beaufort Gyre Phenomenon: Multicomponent System Mechanisms Amentioning
confidence: 99%
“…The lack of a planetary beta effect and weak dissipation result in a highly efficient inverse energy cascade that increases the equilibrium eddy size. These relatively large simulated eddies have the first baroclinic mode structure, being distinct from the O(10 km) higher baroclinic mode eddies detected by, for example, BG moorings (Zhao et al, ). Yet the salinity transport done by these large‐scale eddies is sufficiently strong to arrest the halocline deepening at a depth comparable to observations.…”
Section: Idealized Bg Model With Continental Slopesmentioning
confidence: 99%
“…These eddies are large‐scale and deep. Because of the lack of surface buoyancy forcing, our idealized BG model does not generate a realistic mixed layer or any other isopycnal outcroppings, thus inhibiting the formation of higher baroclinic mode eddies—more energetic and localized eddies with peak velocities centered in the halocline that are commonly observed in BG moorings and Ice Tethered Profilers (Zhao et al, , ). By construction, the cumulative salt transport by the modeled large‐scale eddies must exactly counteract the Ekman transport and this balance leads to a realistic halocline depth of O(100 m).…”
Section: Eddy Dynamics Over Continental Slopesmentioning
confidence: 99%